MENINGKATKAN GREEN BEHAVIOUR MELALUI LITERACRAFT UNTUK ANAK USIA DINI (Penelitian Tindakan Kelas di PAUD/TK Narfa Izdihaar Kecamatan Cimenyan Kabupaten Bandung Tahun Ajaran 2021 - 2022) - Nenden Nurfita, - (2021)
This research is motivated by the not yet optimal attitude of green behavior of PAUD/TK Narfa Idzihaar children, Cimenyan District, Bandung Regency and the difficulty of teachers in explaining material about green behavior to children. An appropriate method is needed to improve the green behavior of children in PAUD/TK Narfa Izdihaar, namely through literacraft. The purpose of this research is to improve green behavior through literacraft in early childhood in PAUD/TK Narfa Izdihaar, Cimenyan District, Bandung Regency. This study uses the Classroom Action Research (CAR) method which was adapted from the Kemmis and McTaggart cycle with a qualitative approach. This research was conducted in three cycles and is a collaboration between researchers and teachers to improve green behavior through literacraft in PAUD/TK Narfa Izdihaar. The results of this study indicate that the green behavior of Narfa Idzihaar's PAUD/TK children, which was not optimal at first, after going through treatment literacraft showed an increase. Children are able to distinguish between organic and anorganic waste, dispose of waste in its place, distinguish between healthy and unhealthy food, and adopt recycling behavior. The attitude of green behavior through literacraft is based on the knowledge, practice and care gained during crafting and literacy projects. Keywords: green behaviour, literacraft, early childhood.